Licensing Open Data in Developing Countries: The Case of the Kenyan and City of Cape Town Open Data Initiatives - Michelle Willmers; François van Schalkwyk; Tobias Schonwetter (The African Journal of Information and Communication, 2015)
Open data practice is gaining momentum in the public sector and civil society as an important mechanism for sharing information, aiding transparency, and promoting socio-economic development. Within this context, licensing is a key legal mechanism that enables re-use without sanction. However, there is evidence of a “licensing deficit” and this raises questions regarding best practice and sustainability in emerging African open data initiatives, particularly in the context of intermediaries being encouraged to exploit shared data for economic and social benefit. This article asks two main questions: (1) What is the current state of open licensing in two African open data initiatives; and (2) to what degree is it appropriate to focus on licensing as a key indicator of openness? Utilising a case study approach, the research explored licensing dynamics in the Kenya Open Data and the City of Cape Town Open Data initiatives, examining the contexts in which these initiatives were established and their resulting licensing frameworks. The cases reveal evidence of strategic engagement with content licensing, driven largely by the need for legal protection, adherence to international best practice and attraction of the user base required in order to ensure sustainability. The application of licensing systems in both contexts does, however, suggest an emerging system in which data providers are “learning by doing” and evolving their licensing practice as portals and their associated policy frameworks mature. The paper discusses the value of open data licensing as an indicator of organisational change and concomitant importance of taking into consideration the institutional dynamics when evaluating the organisational licensing frameworks of city, national and other governments.